Productivity and technological qualities of Grom winter wheat grain variety depending on the application of plant growth regulators and nitrogen top dressings - A. A. Makarov; N. I. Mamsirov; Z. A. Ivanova; F. Kh. Tkhazeplova (Новые технологии)
The article presents the results of a multi-year research aimed at establishing the influence of plant growth regulators and doses of nitrogen top dressings on the growth, development, productivity and technological qualities of Grom variety of soft winter wheat grain of the FSBSI «SGC named after P.P. Lukyanenko» selection. The results of the research revealed that the duration of the entire growing season and interphase stages of winter wheat development was largely influenced by weather conditions in the spring-summer period. Application of nitrogen top dressing in the «tillering-beginning of stemming» phase promoted the formation of more vigorous winter wheat plants with an increased tillering coefficient. The best indicators were obtained in options where «Biosil» preparation was used. The most intensive increase in the aboveground mass of winter wheat throughout the growing season occurred with the use of the «Alfastim» growth regulator; it was followed by «Novosil» preparation. The cultivation of crops with growth regulators increased the productive plant stand by 7,8–15,2%, but didn’t have a significant effect on the other elements of the crop structure. Application of nitrogen fertilizer in doses of N35+N35 иN35+N35+N20 when treated with «Novosil» growth regulator provided a high yield – up to 7,13 t/ha. Slightly lower was the yield with the use of «Alfastim» preparation compared with «Novosil». In the option without nitrogen fertilizers the fifth class grain was formed, and the treatment of winter wheat crops with the studied preparations increased the class of grain to the fourth one, due to an increase in the content of protein and gluten in the grain. Similar changes were also noted when nitrogen was added to the top dressing at doses of N20 + N20 and N35 + N35. Spring nitrogen fertilization of winter wheat crops in the heading phase contributed to an increase in the grain class.